Anxiety disorders pharmacological and non-pharmacological methods of therapy - Truchta, Monika; Mańkowska, Aleksandra; Jabłońska, Wiktoria; Wardęszkieiwcz, Marta; Kasprzak, Amelia; Markowiak, Szymon; Świercz, Maciej; Kolano, Agata; Pejas, Anna (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Anxiety disorders are a heterogeneous cluster of common mental health disorders typically characterized by hyperarousal, excessive fear and worry. Unfortunately, a large portion of the world's population does not have access to traditional mental health care, this is influenced by the paucity of available psychiatric services, particularly in many low- and middle-income countries. This article will discuss how patients suffering from depression or anxiety disorders turn to non-pharmacological and unconventional interventions such as exercise, yoga, meditation, aromatherapy or music therapy. The aim of study: The purpose of this literature review was to assemble and analyse the available data about anxiety disorders. Material and method: Standard criteria were used to review the literature data. The search of articles in Pubmed database was carried out using following keywords: Anxiety disorders; depression; mental illness; alternative treatment methods. Description of the State of Knowledge: Pathologically increased anxiety is found not only in anxiety disorders per se, but also in most other types of mental illness. The first-line methods are pharmacotherapy and cognitive-behavioral therapy. Of particular interest is the use of physical activity and exercise in the treatment of anxiety disorders. This treatment is inexpensive and has few undesired effects. Exercises such as yoga, meditation, tai chi or qi gong are becoming more and more popular. Summary: Anxiety disorders can now be treated effectively. Current research focuses on individualized forms. We hope that even more effective methods of therapy will be developed than those currently available. Keywords: Anxiety disorders; depression; mental illness; alternative treatment methods.